50 Gb/s DMT and 120 Mb/s LTE signal transmission over 5 km of optical fiber using a silicon photonics transceiver - Rahim, Abdul; Abbasi, Amin; Shahin, Mahmoud; Sequeira André, Nuno; Richter, André; Kerrebrouck, Joris Van; Van Gasse, Kasper; Katumba, Andrew; Moeneclaey, Bart; Yin, Xin; Morthier, Geert; Baets, Roel; et al. (In Integrated Photonics Research, Silicon and Nanophotonics, 2018)
Next-generation passive optical networks will require the use of low-cost, high-performance transceivers to cope with the increasing bandwidth demands for emerging applications such as fixed-mobile convergence for 5G. Silicon photonics is widely acknowledged as a technology that can provide manufacturing of low-cost photonic integrated circuits by using existing CMOS fabrication infrastructure. Intensity modulation/direct detection solutions can reach 100 Gb/s per wavelength, but require high-speed electronics and photonics, which adversely affects the cost. An alternative approach is to use advanced multi-carrier modulation schemes, such as Discrete Multi-Tone (DMT), a real-valued Orthogonal Frequency Division Multiplexing (OFDM) scheme. This technique uses Digital Signal Processing (DSP) to relax electrical and optical bandwidth requirements on the transmitter and receiver side. It promises high spectral efficiency and granularity, higher tolerance to fiber impairments and channel adaptation through flexible multi-level / multi-carrier coding [1]. DMT transmission at 100 Gb/s and even 4x100 Gb/s using modest bandwidth (~ 20 GHz) electronic and optical components has already been demonstrated [2-4]. Despite requiring computationally more expensive DSP compared to single carrier baseband schemes (e.g., OOK, PAM), DMT’s added advantage is that it allows transmission of a mobile data signal within its bandwidth using the same optical transceiver [5]. In this work we demonstrate the combined transmission of a Long Term Evolution (LTE) 4G mobile communication signal (at 3.48 GHz carrier frequency) and a 50 Gb/s DMT signal using a directly modulated InP-on-Silicon Distributed Feedback (DFB) laser. Direct modulation is poised to provide low power consumption and a reduced number of optical components in the transceiver. On the receiver side, a silicon-waveguide-coupled germanium photodiode (GeSi-PD) with a co-designed trans-impedance amplifier (TIA) is used and its performance is compared with a commercial III-V photodiode and TIA.
Keywords: Gb/s DMT; LTE signal transmission; Optical fiber; Silicon photonics transceiver